Disharmonisasi Struktur Sanksi Pidana dalam Konservasi Keanekaragaman Hayati terhadap Kebijakan Pertambangan di Ekosistem Karst - Aerlangga Kusumah Nur Putra; Gialdah Tapiansari Batubara (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The complexity of environmental issues in Indonesia is escalating due to unsustainable exploitation of natural resources, particularly in vulnerable karst ecosystems affected by mining activities. Karst ecosystems, featuring unique hydrological functions and high biodiversity, often suffer irreversible damage such as groundwater degradation and loss of endemic habitats from illegal or environmentally unfriendly permitted mining.The case of kumbung stone mining in Tuban, East Java, exemplifies regulatory disharmony between conservation and mining laws. This study emphasizes the need to harmonize criminal sanctions between Law No. 32/2024 and Law No. 4/2009 to protect karst ecosystems, alongside environmental law enforcement solutions. Using a normative juridical approach grounded in Pancasila and the 1945 Constitution, it proposes regulatory revisions, enhanced sanctions (billions in fines, longer imprisonment, ecosystem restoration), mining permit moratoriums, independent audits, and community involvement to create deterrent effects and support sustainable development.